New Zealand and Costa Rica: An Analysis from the Caribbean - Morales Delgado, Jorge (2023)
In this work, we undertake the task of analyzing the social and cultural similarities and differences underlying the identity construction processes inNew Zealand and Costa Rica. In particular, we carry out an analysis of the consolidation mechanisms of national identities in New Zealand from a perspective ofthe costarican Caribbean. In this process, we underline the particularities of both social realities and the interaction with the practices and hegemonic narratives in each country.